PENGARUH PENGEMBANGAN KARIR, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR AKUNTAN PUBLIK MOCH. ZAINUDDIN, SUKMADI & REKAN - Jullanar, Ghina; Recky, Recky; Surjaatmadja, Surachman (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This study aims to analyze the influence of Career Development, Work Motivation, and Work Discipline on Employee Performance. A quantitative approach was employed with a population of 30 employees, and data were analyzed using SEM-PLS. The results reveal that Work Discipline significantly impacts Employee Performance with a path coefficient of 0.634 (t-statistics 5.598). Conversely, Work Motivation (path coefficient 0.078; t-statistics 0.848) and Career Development (path coefficient 0.143; t-statistics 1.621) do not show significant effects. The R Square value of 0.638 indicates that the model explains 63.8% of the variance in Employee Performance. These findings highlight Work Discipline as a key factor in improving Employee Performance, while Work Motivation and Career Development require more specific approaches to have a significant impact. This study contributes to the literature and managerial practice by emphasizing the importance of managing work discipline to achieve optimal performance.